Interferon-γ-inducing factor (IL-18) and interferon-γ in inflammatory CNS diseases - Faßbender, Klaus; Mielke, Orell; Bertsch, Thomas; Muehlhauser, F.; Hennerici, Michael G.; Kurimoto, M.; Rossol, Siegbert (Neurology, 1999)
OBJECTIVE: To examine the intrathecal production of a newly identified cytokine, interferon-gamma-inducing factor (IL-18), together with interferon-gamma itself, in inflammatory diseases of the CNS (i.e., bacterial meningitis, viral meningoencephalitis, and MS). - RESULTS: IL-18 concentrations in CSF were significantly increased in bacterial meningitis and tended toward increased levels in viral meningoencephalitis. In contrast, IL-18 was detectable only in a few patients with MS and healthy controls. Interestingly, interferon-gamma was significantly increased selectively in CSF of patients with viral meningoencephalitis. - CONCLUSION: The observation of an intrathecal release of IL-18 in patients with meningitis argues for a pathophysiologic role of this novel cytokine in immunity against invading microorganisms the CNS.